Infant Condition in Pregnant Mothers with Covid-19 - Neli Sunarni; Aulia Ridla Fauzi; Sri Wulan Ratna Dewi; Yanti Herawati (Yayasan Inspirasi El Burhani, 2022)
Introduction: At the end of December 2019, a case of pneumonia with an unknown cause was reported, which became a new outbreak, starting in Wuhan Area, Hubei Province, China. The disease that is endemic to almost all of the world is Coronavirus Disease 2019 (COVID-19). In Indonesia, as of July 11, 2020, as many as 74,018 confirmed COVID-19, this has become a major global health problem. COVID-19 can affect anyone, including pregnant women. However, it is noted from several studies showing the mild severity of infection in pregnant women with COVID-19 still requires special attention related to monitoring the condition of the baby in the womb. Common symptoms include fever, coughing, and chest pain. Aim: The purpose of this review literature is to describe the state of babies born to pregnant women with COVID-19. Method: The method was used a literature review by searching for articles published in various databases, including Medline, Science Direct, Cochrane using appropriate keywords (pregnancy, vertical transmision, perinatal, neonatal, SARS-CoV-2, COVID-19) from March to March June 2020. Results: Results from a review of 6 articles show the condition of babies born to pregnant women with COVID-19 in good health, APGAR scores well, no vertical transmission from mother to fetus, test results of amniotic fluid, umbilical cord blood, neonatal throat swabs and ASI samples were not detected by COVID-19. Conclusion: The conclusion based on the literature review that has been done is the condition of babies born to pregnant women with COVID-19 in a healthy state and found no severe complications